PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sihombing, Dami Yanti; Munthe, Kornel (UNIKA Santo Thomas, 2018)
This study aims to determine and analyze the effect of financial performance on stock prices on plantation companies listed on the Indonesia Stock Exchange. The research population is all plantation companies listed in Indonesia Stock Exchange 2007 - 2010 as many as 7 companies. This population is also a research sample. Data were collected through documentation techniques. Data analysis technique used is multiple linear regression. From the results of the discussion can be concluded that partially that the current ratio, total asset turnover, and return on equity have a significant positive effect on stock prices, while debt ratio has a negative and significant effect on stock prices. Simultas current ratio, debt ratio, total asset turnover, and return on equity have a significant effect on stock prices at plantation companies listed in Indonesia Stock Exchange